2020
DOI: 10.1016/j.foodchem.2019.125742
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, antioxidant activity, and inhibitory effect on pancreatic lipase of extracts from the edible insects Acheta domesticus and Tenebrio molitor

Abstract: Extracts from the edible insects Acheta domesticus and Tenebrio molitor were obtained by ultrasound-assisted extraction (UAE) and pressurized-liquid extraction (PLE) using ethanol (E) or ethanol:water (E:W). Characterization by GC-MS was performed and total phenolic compounds (TPC), antioxidant activity (DPPH) and pancreatic lipase inhibitory capacity were assayed.Most extracts, mainly ethanolic extracts, predominantly presented lipids as free fatty acids, followed by aminoacids, organic acids, carbohydrates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 34 publications
15
96
0
4
Order By: Relevance
“…The highest antiradical activity values against both ABTS •+ and DPPH • were observed for the mealworm flour (0.67 and 2.70 mM TE, respectively). Navarro del Hierro et al [34] studied the DPPH • scavenging activity of mealworm extracts and also confirmed their strong antioxidant properties. As expected, the partial substitution of wheat flour with mealworm flour significantly (p < 0.05) increased the free radical scavenging capacity, as reflected by DPPH • and ABTS •+ scavenging activity values.…”
Section: Antioxidant Propertiesmentioning
confidence: 84%
“…The highest antiradical activity values against both ABTS •+ and DPPH • were observed for the mealworm flour (0.67 and 2.70 mM TE, respectively). Navarro del Hierro et al [34] studied the DPPH • scavenging activity of mealworm extracts and also confirmed their strong antioxidant properties. As expected, the partial substitution of wheat flour with mealworm flour significantly (p < 0.05) increased the free radical scavenging capacity, as reflected by DPPH • and ABTS •+ scavenging activity values.…”
Section: Antioxidant Propertiesmentioning
confidence: 84%
“…No studies on human subjects were available. Table 1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) shows the studies investigating the in vitro antioxidant activity of edible insects and invertebrate fractions. Several methods were taken into account: the most used was the 1,1-diphenyl-2-picrylhydrazyl (DPPH), performed in 14 papers (7-15, 18-20, 23, 24), while 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing Abbreviations: 8-OHdG, 8-hydroxy-2 ′ -deoxyguanosine; ABTS, 2,2 ′ -azino-bis(3ethylbenzothiazoline-6-sulfonic acid); CAT, catalase; DPPH, 1,1-diphenyl-2picrylhydrazyl; CP, compound; FRAP, ferric reducing antioxidant power; GHG, greenhouse gas emissions; GPx, glutathione peroxidase; GST, glutathione Stransferase; LS, lipo-soluble extract; MDA, malondialdehyde; NO, nitric oxide; Nrf2, Nuclear factor erythroid 2-related factor; ORAC, oxygen radical absorbance capacity; PH, protein hydrolysates; RNS, reactive nitrogen species; ROS, reactive oxygen species; SAHR, scavenging activity on hydroxyl radicals; SOD, superoxide dismutase; SRSC, superoxide radical scavenging capacity; TAC, total antioxidant capacity; TEAC, Trolox equivalent antioxidant capacity; TOS, total oxidant status; WI, whole insect; WS, water-soluble extract.…”
Section: Search Strategymentioning
confidence: 99%
“…Antioxidant activity was investigated also as scavenging activity against different radicals, metal ion chelating activity, reducing power, or, only for the paper of Sun et al (25), with β-carotene and linolenic acid bleaching tests. Nineteen studies were carried out, involving 30 species of insects; of these, the most studied was Tenebrio molitor, cited in nine papers (6-10, 13-16), followed by Acheta domesticus (6,8,9) and Gryllodes sigillatus (7,19,20), tested in three papers, and Bombyx mori (6,11), Hermetia illucens (21,22), and Lethocerus indicus (6,24) in two papers. Water-soluble fractions were tested in 12 papers (6, 9-15, 17, 18, 20, 24), protein hydrolysates were evaluated in 6 research articles (7,8,16,19,21,22), while lipo-soluble fractions were reported in 2 papers only (6,23).…”
Section: In Vitro Antioxidant Activities Of Edible Insectsmentioning
confidence: 99%
“…Several authors found polyphenolic compounds in flours or extracts obtained from numerous insects. Thus, Navarro del Hierro et al. (2020) reported that the phenolic content of lyophilized flours obtained from A. domesticus and T. molitor using different extraction methods and solvents ranged between 0.3 and 5 g GAE/100 g for A .…”
Section: Resultsmentioning
confidence: 99%